Lower white blood cell counts in elite athletes training for highly aerobic sports - Horn, P. L.; Pyne, D. B.; Hopkins, W. G.; Barnes, C. J. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Evaluation of full blood-cell counts is a standard diagnostic test, but sports-specific reference ranges have not been established for elite athletes. Although it is generally recognized that exercisers have lower white blood cell counts than sedentary folks, it is unclear whether cell counts vary substantially between sports, sex and ages of elite athletes. Methods We retrospectively examined blood test results of rested, healthy athletes (presenting without illness) collected over a 10-y period in a haematology database linked with demographic information on age, sex, and sport. Reference ranges were established for 14 sports consisting of 3,679 samples from 937 females aged 20.9 ± 2.1 y (mean ± SD) and 4,654 samples from 1310 males aged 21.4 ± 2.3 y. Total white blood-cell counts and counts of neutrophils, lymphocytes and monocytes were quantified with an automated haematology analyser. To characterise the influence of metabolic (aerobic vs anaerobic) and mechanical (concentric vs eccentric) stress of a sport on differences in cell counts, we used 2SD of a five-point Likert scale from 13 sports physiologists. Results The white blood cell counts of elite athletes were generally lower than those of the population reference ranges but age and sex did not have substantial effects on cell counts. Substantially lower white blood cell and neutrophil cell counts were observed in the aerobic sports of cycling and triathlon (~16% of test results below the lower limit of the population reference range) compared with team or skill-based sports such as water polo, cricket and volleyball (~1.8% of results). The apparent degree of eccentric muscle contractions between sports did not substantially affect the distribution of cell counts. Discussion/Conclusion White blood cell counts (total and sub-types) can be lower in elite athletes participating in aerobic sports. The lower counts probably represent an adaptive response in healthy athletes rather than an underlying pathological response.